High sensitivity au-based Kretschmann Surface Plasmon Resonance sensor for urea detection - P. Susthitha Menon; Fairus Atida Said; Gan, Siew Mei; Mohd Ambri Mohamed; Ahmad Rifqi Md Zain; Sahbudin Shaari; Burhanuddin Yeop Majlis (Penerbit Universiti Kebangsaan Malaysia, 2019)
Kretschmann-based Surface Plasmon Resonance (SPR) optical sensor was applied to detect the presence of kidney wastes such as urea in solutions. To enhance the sensitivity of the SPR sensor, nanolaminated gold film (thickness of 50 nm) was used. In this work, the SPR response to urea in various concentrations were measured and investigated using optical wavelengths of 670 nm and 785 nm. The signals were compared between pure urea solution versus mixed solution in the presence of the 0.227 μmol urease enzyme. The proposed mixed solution is to eliminate doping and gel entrapment process for enzyme immobilization in conventional method. Angular interrogation technique was used to measure the sensor performance in urea detection using pure and mixed solutions with urea concentration of 0 - 800 mM. Upon exposure to mixed solution using 785 nm optical wavelength, the nanolaminated gold film exhibited higher SPR sensitivity as much as 7.8 M-1 than a pure urea solution (1.4 M-1). The coupling activity between urea and urease molecules in the mixed solution near the nanolaminated gold film surface lead to sensitivity enhancement. Angle shifting of mixed solution on 50 nm-thick nanolaminated gold film using 670 nm optical wavelength was greater by ~50% compared to 785 nm. Sensorgram data shows a steady and linear increment in SPR incident angle shifting when urea concentration increased. To the best of our knowledge, this is the first time that Kretschmann-based SPR has been used for urea sensing at 670 nm and 785 nm optical wavelengths.